Interaction Of Family and Peers on Entrepreneurship Intentions - Fernando Saragih; Indra Mulia Pratama; Christina Natalina Saragi; Lastri Wahyuni Manurung; Krisna Wati Mayang (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACTEntrepreneurial intention is one of the right solutions to spur economic growth. Where this intention is strongly influenced by various factors, one of which is the environment. Based on this explanation, the researcher wants to focus on knowing how environmental variables (family and peers) influence the entrepreneurial intention variable (through the theory of planned behavior). Its process, this research is based on quantitative research (with the expo facto method) which focuses on questionnaires as the research instrument (using 111 respondents with accidental sampling). In addition, this research has also been said to be feasible and can be continued because it has fulfilled all the requirements starting from the instrument test and classical assumptions. Based on the analysis process (multiple linear regression analysis with SPSS 23), the results obtained explain that there is a positive and significant influence between the family environment and peers on entrepreneurial intentions (0.573 and 0.489).Keywords: Entrepreneurial intention, family, peer.